Wytwarzanie wartości ekonomiczno-społecznej a zmiany obowiązującego sposobu gospodarowania - Olszewska, Monika (Annales. Etyka w Życiu Gospodarczym, 2013)
The article presents the idea that the maximisation of profit seems not to be the most important goal for contemporary enterprises. The author – basing on literature and empirical research – tries to indicate those activities undertaken by enterprises in the interest of the local community that have an impact not only on building managers’ mental well-being and quality of life. They are also different kinds of CSR activities, but they could also be considered as proof of changing the economic model. The article ends with conclusions in which the author tries to answer the following question: what kind of profit could bring about the realisation of that new model.